Soybean Cultivation Technology and Basics of Land Preparation for Planting - Kholliyev Askar Ergashovich; Aminjonova Charos Akmalovna (Genius Journals, 2022)
This article discusses the cultivation of soybeans and its importance in agriculture, planting, care and its fertility in the agriculture of the republic, depending on the conditions of the regions. In addition, methods of preparing land for sowing were discussed, ideas and opinions were expressed on ways to increase the yield of soybean crops.
Keywords: Organic Matter; Mineral Fertilizers; Cultivation; Soil